Skeletal Vibrations in Sulfur-Dioxode Complexes of Ruthenium(II) - Breitinger, Dietrich; Breiter, Roman (Journal of Molecular Structure, 1995)
In connection with X-ray structure analyses the vibrational spectra of the sulfur dioxide complexes [RuX(SO2)(NH3)4]X (X = C1 and Br) (1 and 2, 1 also in deuterated form) and [Ru(OH2)(SO2)(NH3>(4)](BF4)(2) (3) with S-coordinated SO2 ligands have been measured and the most important aspects of the skeletal modes discussed. In all cases the valence vibrations v(as) and v(s) of the SO2 ligands are lower in frequency than the respective vibrations of free SO2, while the delta(SO2) appear at higher frequencies. IR and Raman bands around 420 and 330 cm(-1) are assigned to librations of the SO2 ligands. The high frequencies of v(RuS) around 350 cm(-1) reflect the short Ru-S bonds. The valence vibrations v(RuN4), shifted on deuteration, are found in the range 480 to 430 cm(-1) and yield approximate force constants f(RuN) (198, 191, and 184 Nm(-1) for 1, 2, and 3, respectively). The v(RuX) bands (X = Cl, Br, and OH2) at 276, 190, and 498 cm(-1), respectively, are surprisingly weak in both IR and Raman spectra.